Defining velocity and acceleration ranges for time-motion analysis from a 7-sided game in U11 soccer players using global positioning system devices: a case study - Abaïdia, A.-E.; Dupont, G.; Baquet, G. (Journal of Science in Sport and Exercise, 2023)
The aims of this study were (1) to define speed and acceleration thresholds from youth match activity of soccer players and (2) to analyze the activity performed by young soccer players during a match using GPS devices and according to these thresholds. Ten U11 soccer players from a professional club participated in a 7-sided match being equipped with global positioning system (GPS) devices (sampling frequency 5 Hz) to measure the speed of each player. The Kernel Density Estimate (KDE) was used to observe the occurrences of velocities. The range of velocities was described by a distribution curve, from which the speed and acceleration thresholds for each category of movement were defined and time-motion analysis of the match was made. The model with 4 Gaussian laws was the best when using the Akaike Information Criterion (AIC). In this study, the thresholds defined for each category of movement were: standing (< 0.1 km/h), walking (0.1-5.6 km/h), slow running (5.7-7.7 km/h), fast running (7.8-12.7 km/h) and sprint (= 12.8 km/h). Acceleration thresholds were calculated to define movement considered as a sprint for each category of movement: standing (0.3 m/s2), walking (0.66 m/s2), slow running (1.01 m/s2) or fast running (0.97 m/s2). All the acceleration thresholds were significantly different from each other (P < 0.001) with large effect sizes, excepting the comparison between slow and fast running (P = 0.41) with a small effect size. In U-11 soccer players, time-motion analysis may be performed according to five categories of movement. This study has also defined sprint and acceleration thresholds for this category of age.